O poder do mito na construção do caos: mitos, símbolos, ritos e as forças ocultas no nazismo - Oliveira, Damião Costa de (2017)
This dissertation aims to reflect on the term myth. The purpose is to identify, analyze and establish relations between the various forms of myth and Nazism, in order to understand to what extent the myth was the cause of the social disturbances in Germany and consequently in other societies. We will try to show that the rise of Nazism between 1933 and 1945 came partly from the unresolved problems of the end of World War I, which involved a complex chain of events, such as revanchism, nationalism, military alliances and territorial expansionism. In this context, myth has found the ideal conditions for causing social disorder. The myth has often been overlooked by some authors, which proved to be a great mistake since it has been one of the main factors throughout the social and political history of humanity and, unnoticed by societies, revealed all its power in the thirties and forties resulting in World War II. The human inability to deal with the consequences of myth - that are strengthened in periods of threat and overlap other social forces and reason - were able to change the history of humanity and the lives of millions of people